3D graphene based materials for energy storage. Issue 5 (October 2015) - Fan, Xueliu; Chen, Xuli; Dai, Liming
Abstract: Three-dimensional graphene based materials have attracted great attention as they not only possess the intrinsic properties of graphene, but also provide high specific surface area, low density, good electrical conductivity, and excellent mechanical properties. As a consequence, three-dimensional graphene materials have been extensively studied for various potential applications, including supercapacitors and batteries for energy storage. Here, we present a focused review on recent progresses and challenges in the synthesis of three-dimensional graphene materials and their applications in energy storage devices. Graphical abstract: